2014
DOI: 10.4018/ijegr.2014010103
|View full text |Cite
|
Sign up to set email alerts
|

Wrestling with Contradictions in Government Social Media Practices

Abstract: Research in government social media practices highlights expectations of co-creation and progression mirrored in maturity models, but research also documents low deployment degree and thereby points to a discrepancy. The paper suggests that the authors instead of co-creation and progression draw on a dialectical approach and understand the development of government social media practices as a wrestling with contradictions. The case of emerging social media practices in a Danish municipality used to illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Changes to organizational structure are not easy for governments that are limited by laws regarding data sharing (Gant & Gant, 2002) that prevent interaction and integration between government departments and agencies. Also, governments lack dedicated SM departments or managers (Haahr, 2013). Whereas the expected result was to find more SMP where more citizens were, given the technological challenges governments face, this finding leads to the conclusion that SM may in fact be a distraction from already established processes.…”
Section: Total Population and Misleading Smpmentioning
confidence: 98%
See 2 more Smart Citations
“…Changes to organizational structure are not easy for governments that are limited by laws regarding data sharing (Gant & Gant, 2002) that prevent interaction and integration between government departments and agencies. Also, governments lack dedicated SM departments or managers (Haahr, 2013). Whereas the expected result was to find more SMP where more citizens were, given the technological challenges governments face, this finding leads to the conclusion that SM may in fact be a distraction from already established processes.…”
Section: Total Population and Misleading Smpmentioning
confidence: 98%
“…Because SM is seen as a vehicle to increase effectiveness and legitimacy by communicating with internal and external stakeholders (Mijer & Thaens, 2013), researchers have explored the adoption and use of SM in government (e.g., Hong, 2013;Mijer & Thaens, 2013;Mossberger, Wu, &Crawford, 2013;Oliveira & Welch, 2013;Reddick & Norris, 2013;Bertot, Jaeger, & Hansen, 2012;Bonsón et al, 2012). Past research concluded the same patterns for SM as EGOV in general: SM is present, can and has produced positive outcomes (Mijer & Thaens, 2013), but is largely in an early and experimental stage of development (Bonsón et al, 2012) and expectations fall short of reality (Haahr, 2013).…”
Section: Social Media In Governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…When a wrestler gets a shorter opponent, for him it will be easy to fade out his balance and the taller wrestler will control the match. The average wrestler with a higher body has a deficiency in the strength of his opponent, so to fight it requires the use of a long range to then be able to reach the opponent's ankle [29]. With this movement, usually the tall wrestlers manage to execute well and take advantage perfectly.…”
Section: A Basic Wrestling Technique (Leverage)mentioning
confidence: 99%
“…Kromidha 2012;Vander Elst & De Rynck, 2014), technology-related issues (cf. Cordella & Bonina, 2012;Cordella & Tempini, 2015;Gong & Janssen, 2012;Haahr, 2014;Meier, Ben & Schuppan, 2013;Mergel, 2013;Orlikowski, 1992) as well as the employer"s perspective and their individual change process (Meier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%